Relationship between understanding of COVID-19's infographics and the efforts to prevent COVID-19 transmission - Rahmat Bakhtiar; Hilda Hilda; Krispinus Duma; Riries Choiru Pramulia Yudia (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
The prevention of disease transmission is an effective cost-strategy in controlling COVID-19. The scenario of the control of COVID-19 in Samarinda City consists of 3 phases, namely initial, advanced, and recovery. The outcome of the advanced phase is flattening the transmission curve of the COVID-19 pandemic, with an increased proportion of patients in recovery, and an increased culture of preventing disease transmission in society. This study aimed at knowing the influence of the understanding of COVID-19 infographics on the efforts to prevent COVID-19 transmission at the advanced phase. A survey was conducted via social media from April 21st to April 30th, 2020. The preventive actions for the disease transmission as the dependent variable in this study were social distancing, wearing a mask, washing hands, and efforts to enhance the body’s immunity, while the independent variable was the understanding of COVID-19 infographics updated daily. The results of the study showed that the proportion of the population who understood the infographics well was 79.5%, the community participation in practicing social distancing (81.6%), wearing a mask (50.9%), washing hands as frequently as possible (74.3%), and the efforts to strengthen the body’s immune system (73.6%) with a consistency level of 55.12%. The lowest rate for the activity of social distancing was visiting elders or the people suffering from comorbidities with 54.71%. A good understanding of infographics could increase adherence to the recommendations of social distancing. The implementation of social distancing, wearing a mask, washing hands as frequently as possible, and the efforts to improve the body’s immune system need to be done consistently to prevent the COVID-19 transmission and as a result, the potential transmission could be minimized to optimize the recovery phase and anticipate the possible second wave of the COVID-19 pandemic.